Industri Halal : Kontestasi Label Halal Pada Sektor Makanan di Provinsi Aceh - Fuadi; Ramadhan Razali (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study examines the differences in interpretation of halal labels between actors from micro, small and medium enterprises (MSME) and small and medium sized industries (IKM). Although halal labels function as an indicator of halal products, various interpretations by industry insiders often lead consumers to consider products without halal labels. This study involved respondents from MSME and IKM stakeholders, communities, and observers of the Halal industry in Aceh province. The results show that different interpretations of halal labels are affected by the lack of socialization performed by stakeholders. In general, people are more likely to choose products with the Halal label than those without the label. To maximize the comprehensive implementation of the halal concept, this study recommends that the government establish a monitoring group to strengthen the supply chain of halal products. Therefore, this effort is expected to reduce ambiguity and increase consumer confidence in Halal products in the market.